Komunikasi Kreatif Filantropi Islam: Upaya Meningkatkan Literasi Wakaf Melalui Safari Dakwah BWA Solo - Andik Wibowo; Agus Fatuh Widoyo (Pawarta: Journal of Communication and Da'wah, 2026)
Waqf has significant potential as an instrument of Islamic philanthropy to support sustainable social development. However, public literacy regarding productive waqf remains relatively low, as many people still associate waqf with traditional forms such as mosques, cemeteries, and religious schools. This limitation creates challenges for philanthropic organizations in encouraging broader community participation as waqif. In response, Badan Wakaf Al-Qur’an (BWA) Solo developed the Safari Dakwah Program, which integrates religious preaching with waqf education and fundraising activities. This study aims to analyze the creative communication strategies employed by BWA Solo through the Safari Dakwah Program, focusing on creative message and creative media strategies in enhancing waqif literacy. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving BWA Solo management, fundraising teams, and Safari Dakwah organizers. Data validity was ensured through source and technique triangulation, while analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal that BWA Solo applies creative message strategies through audience segmentation, reconstruction of waqf meanings, multidimensional message appeals (spiritual, emotional, social, and rational), and storytelling techniques. Meanwhile, creative media strategies are implemented through the integration of offline and digital media. Offline communication fosters trust and direct engagement, while digital platforms extend communication reach and strengthen long-term relationships with waqif. The integration of both strategies creates an experiential communication process that bridges spiritual awareness and philanthropic action. This study concludes that effective waqf literacy programs require the integration of creative messages and media strategies tailored to audience characteristics, enabling Islamic philanthropic organizations to enhance public engagement and sustainable waqf participation.